Treatment of intracranial aneurysms using the new Surpass Evolve flow diverter: Safety outcomes and six-month imaging follow-up - Rautio Riitta; Alpay Kemal; Sinisalo Matias; Numminen Jussi (Elsevier Masson s.r.l., 2022)
Background and purpose: Several studies have reported good long-term results in the occlusion of intracranial aneurysms with flow diverter treatment. The aim of this study was to report the safety and six-month follow-up outcomes using the new Surpass Evolve flow diverter in the treatment of intracranial aneurysms.
Materials and methods: Consecutive patients with intracranial aneurysm treated with Surpass Evolve flow diverter in two high-volume neurovascular centers between May 2019 and January 2020 were retrospectively reviewed. Procedure-related complications, aneurysm occlusion (O'Kelly-Marotta grading scale), and clinical outcomes were assessed.
Results: Twenty-nine patients with 30 aneurysms were included in the study. Favorable aneurysm occlusion (O'Kelly Marotta grading scale C-D) at six-month follow-up was achieved in 21/27 (78%) aneurysms. No clinical procedure related thromboembolic complications were encountered. Twenty-three out of 24 patients with unruptured aneurysms treated with Surpass Evolve remained clinically intact at clinical follow-up. There was one fatal hemorrhagic procedure-related complication (3%). In five patients with ruptured aneurysms, no early or late rebleeds occurred from the aneurysms.
Conclusions: Surpass Evolve FD worked technically well with no intraprocedural thromboembolic complications and occlusion rates comparable to other FDs.